The Relationship of Community Attachment and Community Involvement with Sustainable Tourism Development: The Mediating Role of Perceived Effects - Vahidreza farhadi (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2014)
The purpose of the paper was to test the relationship of community attachment and community involvement with sustainable tourism development. The mediating role of perceived effects in local society kashan. Participants were 200 employees (kashan peoples) who were selected by using simple cluster sampling method. All of the participants completed scales of community attachment, community involvement, sustainable tourism development and perceived effects. Data were analyzed with path analysis model by using LISREL software. Results showed that community involvement had a structural effect on sustainable tourism development directly. Community attachment by mediating perceived benefits had an indirect effect on sustainable tourism development. Also, perceived benefits had a direct effect on sustainable tourism development. Perceived costs had a negative and direct effect on sustainable tourism development.